KEEFEKTIFAN PENGGUNAAN MODEL PENGATURAN MAHIR DAN MODEL INVESTIGASI KELOMPOK UNTUK MENINGKATKAN KETERAMPILAN BERCERITA PESERTA DIDIK SMP YANG INTROVER DAN EKSTROVER (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This study aims to determine the effectiveness of the model advanced settings, the effectiveness of the model investigation, and determine which is more effective between the model and the model setup adept at investigating the storytelling skills of students learning introverted and extroverted. This study used an experimental method sample was tells capability class VII students of SMP Negeri 2 Mayong. This study is a test instrument storytelling skills and data analysis techniques used are descriptive statistics and a different test (t-test). The results of the study were (1) the effectiveness of the regulatory model introverted learners proficient on average 80.58 and extroverted learners average 81.47, (2) the effectiveness of the model in the investigation of a group of learners inrover average 73.84 extroverted learners 74.00, and (3) Learning storytelling with advanced regulatory model is more effective than the model of investigation in both groups of students are introverted or extroverted learners. Conclusions proficient regulatory model and the model of effective investigation on learning tells both introverted and extroverted learners, there is a significant difference after the model treated Advance Organizer and model investigations group. His advice teachers can apply the model Advance Organizer telling learners introverted and extroverted